Checklist of the Hydraenidae (Coleoptera) of Turkey, with notes on distribution - Ertorun, Nesi̇l; Jäch, Manfred A.; Kasapoğlu, Ahmet; Darilmaz, Mustafa C. (Zootaxa, 2011)
A checklist of the Hydraenidae recorded from Turkey is presented. The checklist includes data on the distribution and relevant references for 210 species/subspecies: two Aulacochthebius Leach, 113 Hydraena Kugelann, 21 Limnebius Leach, and 74 Ochthebius Leach. On the basis of their current distribution, the established 210 species/subspecies can be classified into 28 zoogeographical categories, grouped into six complexes. The largest number of species belongs to the group of Turkey endemics (49.05 %), which reflects the local character of the fauna.